O mundo que se ouve: uma análise da paisagem sonora dos shopping centers - CASTORINO, Ademir Batista (2012)
The subject of this dissertation aims to discuss the conversion of the soundscape into noise pollution in the shopping centers of metropolitan area of Goiânia, since noise pollution is one of the main agents of degradation of environmental quality and quality of life in urban areas. The empirical research was developed in the following shopping centers: Flamboyant, Buriti, Araguaia and Goiânia, all members of Brazilian Association of Shopping Centers. The scientific method, methodology, techniques and procedures, were divided into three stages: bibliographic and documental research about noise pollution, measurement of Sound Pressure Levels - SPL, development of a Sound Journal and application of surveys to local customers. The results indicate that only a few theses, dissertations and articles developed in Brazil have noise pollution as their main subject, and that the law is not broad and quite outdated. The empirical research, however, has shown that the SPL found in shopping centers has noise levels higher than those established by the World Health Organization - WHO - that's of 70 dB (A) for this kind of place. In the same way, the Sound Journal was enough to found out that human actions (walking, talking, eating, etc.) and the operation of machinery, equipment and tools are responsible for production of noise within the said places, and the application of the surveys showed that customers are exposed to high noise levels, although they don't recognize the mall as a noisy place. However, it has been observed that noise pollution has gone through the bounds of industries, streets and has arrived at shopping centers, causing health damage in those who frequent them.